2008
DOI: 10.1007/s00228-008-0565-8
|View full text |Cite
|
Sign up to set email alerts
|

Starting insomnia treatment: the use of benzodiazepines versus z-hypnotics. A prescription database study of predictors

Abstract: Z-hypnotics were commonly prescribed. Norwegian drug therapy recommendations also suggest a preference for z-hypnotics. The clear predominance of the shorter acting z-hypnotics may be due to the fact that only longer acting benzodiazepines are available in Norway. Reasons for prescribing benzodiazepines may be co-morbid psychiatric illness, such as anxiety, or a belief that benzodiazepine hypnotics are more effective than z-hypnotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 19 publications
2
29
1
Order By: Relevance
“…27 Other international studies have shown an increase in Z-drug use over time while benzodiazepine use decreased, especially among people over 65 years of age. [28][29][30][31] In Canada, prescribing of benzodiazepines and Z-drugs in British Columbia decreased slightly from 1996 to 2006 in older people, but increased in younger segments of the population (females and people with low income). 20 To set our results in the context of other reports and to assess use of these drugs in the oldest and youngest groups, we stratified our population into 3 age groups.…”
Section: Discussionmentioning
confidence: 99%
“…27 Other international studies have shown an increase in Z-drug use over time while benzodiazepine use decreased, especially among people over 65 years of age. [28][29][30][31] In Canada, prescribing of benzodiazepines and Z-drugs in British Columbia decreased slightly from 1996 to 2006 in older people, but increased in younger segments of the population (females and people with low income). 20 To set our results in the context of other reports and to assess use of these drugs in the oldest and youngest groups, we stratified our population into 3 age groups.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported about 50% of all prescribed hypnotics to be zopiclone (Kassam et al, 2006), and another study reported that zolpidem accounted for 11% of all sleep promoting drugs prescribed and zopiclone for 9% (Ohayon et al, 1999). Use of z-hypnotics increases considerably with age and concomitant somatic or psychiatric disease (Hausken et al, 2009;Kassam et al, 2006;Ohayon et al, 1999). Because of the short terminal half-lives (compared to benzodiazepines), few negative effects on daytime vehicle driving would be expected from the use of z-hypnotics.…”
Section: Introductionmentioning
confidence: 93%
“…The chance of a child receiving hypnotics was even bigger when the mother had used benzodiazepine hypnotics. Using benzodiazepine instead of z-hypnotics is related to psychiatric comorbidity 28. In cross-sectional studies an association between children's measured sleep problems and maternal mental health has been found 29–31.…”
Section: Discussionmentioning
confidence: 99%